Role of Cytochrome p450 and Soluble Epoxide Hydrolase Enzymes and Their Associated Metabolites in the Pathogenesis of Diabetic Cardiomyopathy. Issue 3 (September 2019) - Maayah, Zaid H.; McGinn, Erica; Al Batran, Rami; Gopal, Keshav; Ussher, John R.; El-Kadi, Ayman O. S.
Abstract : Abstract: A plethora of studies have demonstrated that cardiomyopathy represents a serious source of morbidity and mortality in patients with diabetes. Yet, the underlying mechanisms of diabetic cardiomyopathy are still poorly understood. Of interest, cytochrome P450 2J (CYP2J) and soluble epoxide hydrolase (sEH) are known to control the maintenance of cardiovascular health through the regulation of cardioprotective epoxyeicosatrienoic acids (EETs) and its less active products, dihydroxyeicosatrienoic acids (DHETs). Therefore, we examined the role of the aforementioned pathway in the development of diabetic cardiomyopathy. Our diabetic model initiated cardiomyopathy as indexed by the increase in the expression of hypertrophic markers such as NPPA . Furthermore, diabetic cardiomyopathy was associated with a low level of cardiac EETs and an increase of the DHETs/EETs ratio both in vivo and in cardiac cells. The modulation in EETs and DHETs was attributed to the increase of sEH and the decrease of CYP2J. Interestingly, the reduction of sEH attenuates cardiotoxicity mediated by high glucose in cardiac cells. Mechanistically, the beneficial effect of sEH reduction might be due to the decrease of phosphorylated ERK1/2 and p38. Overall, the present work provides evidence that diabetes initiates cardiomyopathy through the increase in sEH, the reduction of CYP2J, and the decrease of cardioprotective EETs. Abstract : Supplemental Digital Content is Available in the Text.